Malformations of Cortical Development, Cognitive Involvementand Epilepsy: A Single Institution Experience in 19 Young Patients - Valeria Venti; Maria Chiara Consentino; Pierluigi Smilari; Filippo Greco; Claudia Francesca Oliva; Agata Fiumara; Raffaele Falsaperla; Martino Ruggieri; Piero Pavone (MDPI AG, 2021)
Background. Malformations of cortical development (MCD) include a wide range of congenital disorders mostly causing severe cognitive dysfunction and epilepsy. Objective: to report on clinical features including cognitive involvement, epileptic seizures with response to antiseizure medications, comorbidities in young patients affected by MCD and followed in a single tertiary hospital. Patients and methods: A retrospective review of the medical records and magnetic resonance images (MRI) of 19 young patients with an age ranging between eight days and fifteen years affected by MCD and admitted to Pediatrics Department University of Catania, Italy from October 2009 and October 2020 were selected. Patients were distinguished in three groups following the Barcovich et al. 2012 classification for MCD: 4 (21%) in Group I; 8 (42%) in Group II; and, and 7 (37%) in Group III. Clinical features and MRI of the patients including cognitive involvement, epilepsy type and response to drugs treatment were analyzed. Results: In Group I, two patients showed cortical dysplasia and two dysembryoplastic neuroepithelial tumors plus focal cortical dysplasia; developmental delay/intellectual disability (DD/ID) was severe in one, moderate in one and absent in two; the type of seizures was in all the cases focal to bilateral tonic-clonic (FBTCs), and drug resistant was found in one case. In Group II, three patients showed neuronal hetero-topias and five had pachygyria-lissencephaly: DD/ID was severe in four, moderate in two, and absent in two; the type of seizure was focal (FS) in five, focal to bilateral tonic-clonic (FBTCs) in two, infantile spasms (IS) in one, and drug resistant was found in three. In Group III, six showed polymicrogyria and one schizencephaly: DD/ID was found severe in five, moderate in two, and the type of seizure was focal (FS) in five, FBTCS in two, and drug resistance was found in three.